HUBUNGAN GAMBARAN HASIL PEMERIKSAAN FOTO THORAX DENGAN KEPOSITIVAN HASIL PEMERIKSAAN SPUTUM PADA PENDERITA TB PARU DI RSUD PEMERINTAH KABUPATEN ACEH TIMUR PERIODE JANUARI 2018 - AGUSTUS 2019 - KHEMAL MUBARAQ; FANI ADE IRMA (JURNAL ILMIAH KOHESI, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium Tuberculosis, which can attack variousorgans, especially the lungs. The source of transmission is TB patients, especially patients who contain TB germs in theirsputum. When coughing or sneezing, the patient spreads germs into the air in the form of sputum sputtering (droplet nuclei).Infection will occur if someone breathes in air that contains infectious sputum splashes. One cough can produce about 3000sputum sputum which contains as many as 0- 3500 Mycobacterium Tuberculosis. Meanwhile, if you sneeze can issue asmany as 4500 - 1,000,000 Mycobacterium Tuberculosis. The purpose of this research is to find out the relationship betweenthe description of the results of the thorax photo examination with the results of sputum examination in patients withpulmonary TB in RSUD Sultan Abdul Aziz Syah Peureulak. This type of research is analytic with cross sectional studydesign. The number of samples in this study were 37 respondents obtained using total sampling. The results of this studyindicate there is a relationship between the results of the examination of the chest radiograph with the results of sputumexamination in patients with pulmonary TB (Pvalue = 0,000). Suggestions to all parties, both the RSUD Sultan Abdul AzizSyah Peureulak, the Local Health Service, and the community to work together in deciding the transmission of pulmonaryTB.